Current Topics in Pharmacological Research on Bone Metabolism: Osteoclast Differentiation Regulated by Glycosphingolipids - Satoshi Fukumoto; Tsutomu Iwamoto; Eiko Sakai; Kenji Yuasa; Emiko Fukumoto; Aya Yamada; Tomokazu Hasegawa; Kazuaki Nonaka; Yuzo Kato (Elsevier, 2006)
Abstract.: Glycosphingolipids are thought to play important roles in the development and function of several tissues, although the function of glycolipids in osteoclastogenesis has not been clearly demonstrated. In the present study, D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP), a glucosylceramide synthase inhibitor, completely inhibited osteoclastogenesis induced by macrophage-colony stimulating factor (M-CSF) and receptor activator of NF-κB ligand (RANKL). Following treatment with D-PDMP, nearly all glycosphingolipid expression was dramatically reduced on the surface of bone marrow cells, which suggests that glycosphingolipids are necessary for osteoclastogenesis. To determine which kinds of glycolipids are important for osteoclastogenesis, we added several types of purified glycolipids to D-PDMP treated bone marrow cells, as the precursor of osteoclasts is known to express glucosylceramide (GlcCer) and lactosylceramide (LacCer). Following treatment with RANKL, ganglioside GM3 and GM1 were increased in the treated bone marrow cells, whereas other types were not detected using thin layer chromatography analysis. In cells cultured with those glycolipids, exogenously added LacCer rescued osteoclastogenesis blocking by D-PDMP. Furthermore, receptor activator of nuclear factor κB (RANK) induced the recruitment of tumor necrosis factor (TNF)-associated factors 2 and 6 (TRAF2 and 6, respectively) to the cytoplasmic tail of RANKL with activated IκB kinase and IκB phosphorylation, while D-PDMP treatment inhibited RANKL and induced κB phosphorylation, and that inhibition was recovered by LacCer. In addition, RANK, TRAF2, TRAF6, and LacCer were found localized in lipid rafts on the cell surfaces. These results suggest that glycosphingolipids, especially LacCer, are important for the initial step of RANKL-induced osteoclastogenesis via lipid rafts. Keywords:: glycosphingolipid, lipid raft, lactosylceramide, osteoclast, RANKL (receptor activator of nuclear factor κB ligand)